LCD-Net: A Lightweight Remote Sensing Change Detection Network Combining Feature Fusion and Gating Mechanism - Wenyu Liu; Jindong Li; Haoji Wang; Run Tan; Yali Fu; Qichuan Tian (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Remote sensing image change detection is crucial for monitoring dynamic surface changes, with applications ranging from environmental monitoring to disaster assessment. While traditional CNN-based methods have improved detection accuracy, they often suffer from high computational complexity and large parameter counts, limiting their use in resource-constrained environments. To address these challenges, we propose a lightweight remote sensing change detection network (LCD-Net) that reduces model size and computational cost while maintaining high detection performance. LCD-Net employs MobileNetV2 as the encoder to efficiently extract features from bitemporal images. A temporal interaction and fusion module enhances the interaction between bitemporal features, improving temporal context awareness. Additionally, the feature fusion module (FFM) aggregates multiscale features to better capture subtle changes while suppressing background noise. The gated mechanism module in the decoder further enhances feature learning by dynamically adjusting channel weights, emphasizing key change regions. Experiments on LEVIR-CD+, SYSU, and S2Looking datasets show that LCD-Net achieves competitive performance with just 2.56M parameters and 4.45G FLOPs, making it well-suited for real-time applications in resource-limited settings.